Active zone depth and edge moisture variation distance in expansive soils - Durkee, Dean Brian, author; Nelson, John D., advisor; McWhorter, David B., committee member; Shackelford, Charles D., committee member; Edgar, Thomas V., committee member (Colorado State University. Libraries, 2000)
Two fundamental design parameters for foundations on expansive soils are historically referred to as active zone depth and edge moisture variation distance. The purpose of this research was to investigate these two parameters in terms of their historical definitions, characterize them in terms of the effects of climate conditions, geologic conditions, and soil properties, and estimate the long term active zone depth and edge moisture variation distance at the field test sites. Typical foundation engineering design practice for expansive soils involves the use of active zone depth for the determination of heave and pier length. Previous attempts to define the active zone depth were based on techniques for approximating its value. Common practice along the Front Range in Colorado is to approximate the active zone depth, in the range of 15 to 20 feet, or less based on seasonal fluctuations observed in the natural sods. The edge moisture variation distance is used for the design of reinforcing for slab on grade construction. This parameter has been defined as the distance measured inward from the edge of the slab over which the water content changes in response to climate fluctuations. This definition implies that the edge moisture variation distance is a function of depth. Nelson and Miller (1992) pointed out that the edge moisture variation distance is not clearly defined for the purposes of slab design and that it is the most difficult parameter to estimate. Several methods for determining the edge moisture variation have been developed however they have not been tested and generally give unclear results. A new definition of active zone depth is proposed in this dissertation. The active zone depth is "the zone in the soil beneath a structure that is contributing to the actual heave that takes place at some point at the surface at a given time (t)". As such the active zone depth is a time dependent and spatially dependent parameter. The historical definition of edge moisture variation distance is assumed to be appropriate based on the results of this research. Two simulated slabs-on-grade were constructed to study these two design parameters and to evaluate the definitions presented above. In addition, the test sites provided data for analyses of the effects of climate, geology, and soil properties. One simulated slab was constructed at the CSU Expansive Soils Test Site at Colorado State University in Fort Collins, CO and one at the Waterways Experiment Station Expansive Soils Test Site at Fort Sam Houston in San Antonio, Texas. In addition, laboratory tests were conducted on soils from both sites for use in the analyses. Finally, numerical modeling was conducted to consider the long-term effects of boundary condition changes at the CSU site. Based on the results of the field and laboratory investigations and numerical modeling conducted for this research the follow key observations and conclusions lend credibility to the proposed definition, of active zone depth and historical definition of edge moisture variation distance presented above. • The zone of seasonal moisture fluctuation significantly underestimates the depth of the active zone. Based on water content data from the CSU site, in the uncovered soil, the depth of seasonal moisture fluctuation is approximately 5 to 7 feet. Water content increases beneath the slab have been observed as deep as 18 feet. • Initial increases in water content in expansive soil due to the construction of a slab typically result due to the reduction in evaporation at the surface. This boundary change causes an increase in moisture to a depth that is generally consistent with the depth of seasonal moisture fluctuation. However, additional water content increases occur in soils deeper than the depth of seasonal moisture fluctuation resulting in an edge lift condition of the slab. These additional water content increases are the result of infiltration from extreme climatic events and irrigation in the uncovered soils adjacent to the slab. • Continual increases in the depth of active zone generally follow short periods of no increase and tend to coincide with an increase in the rate of rainfall accumulation. When the rate of rainfall accumulation increase coincides with an increase in temperature the thermal gradient causes an increase in downward flow from the warmer to the cooler regions of the soil. During these periods lateral migration of moisture beneath the slab increases the depth of the active zone. This cyclical behavior will continue indefinitely. • Climate conditions, geologic conditions, and soil properties control the rate of increase in the depth of the active zone. In general the availability of moisture is controlled by climate conditions as described above. However, the addition of water from irrigation exacerbates the problem. In addition, preferred flow paths due to geologic conditions such as bedding planes also provide conduits for flow. Hydraulic conductivity and water retention properties primarily affect time rate of development of the active zone. • Based on model results presented herein, the long-term active zone depth for a residential foundation at the CSU test site where irrigation is applied in accordance with Northern Colorado Water Conservancy District guidelines approaches the depth of potential heave based on stress conditions, which is equal to 35 feet. • The edge moisture variation distance measured in this investigation is equal to half the slab width, 15 feet. Therefore to determine the maximum extent of edge moisture variation distance a larger slab would be necessary.
Keywords: civil engineering; geotechnology; hydrology; hydrologic sciences